Bentuk dan Makna Tuturan Upacara Pelulukng Suku Dayak Benuaq di Kalimantan Timur: Forms and meanings of speeches for the “pelulukng” ceremony in the Dayak Benuaq tribe in East Kalimantan - Sulityowati, Endang Dwi; Mulawarman, Widyatmike Gede; Rokhmansyah, Alfian; Sari, Amalia (Journal of Literature and Education, 2023)
This study aims to understand the form and meaning of speech in the Dayak Benuaq tribe's Pelulukng (Traditional Marriage) ceremony. The method used in this research is the semiotic method which is used to understand the form and meaning of speech, especially icons, symbols, and indexes. Data collection methods used include observation and interviews, as well as using tapping techniques. From the research results, it was found that eleven utterances in the form of icons, twelve in the form of an index, and twelve words in the speech in the form of symbols. First, the speech in the form of an icon is a form of action from the Pemeliant because it has similarities or similarities between the speech and the actions taken. Second, speech in the form of an index shows that the utterances spoken by Pemeliant have a cause-effect relationship or contain a causal relationship with the signified. Third, the words in the speech in the form of symbols are the result of the agreement or convention of the Dayak Benuaq community.